Evaluation of Antibiotic Use Patterns at Pharmacy X in Mataram City Using WHO AWaRe Classification - Amira Geys; Deasy Irawati; Metta Octora (Media of Health Research, 2026)
Antimicrobial resistance (AMR) was a major global health threat driven by irrational antibiotic use, including unnecessary prescribing, inappropriate dosage or duration, and use without proper indication. Community pharmacies served as accessible points of care and played an important role in antibiotic distribution, making them strategic settings for evaluating utilization patterns. This study aimed to describe antibiotic utilization in a community pharmacy using the AWaRe classification and to assess the proportion of Access antibiotics relative to World Health Organisation targets. A retrospective observational study was conducted using prescription data from January to June 2025, with purposive sampling and descriptive analysis. A total of 11,565 antibiotic items were recorded. Cefixime (Watch group) was the most frequently used antibiotic (38.2%), followed by amoxicillin (Access group) at 20.9%. The proportion of Access antibiotics was 45.78%, which was below the recommended minimum target of 60%. These findings indicated that antibiotic use was dominated by Watch-group agents, suggesting an imbalance in prescribing patterns and a potential risk for increasing AMR.